Opera for the People - Graf, Herbert, 1903- (Book collections on Project MUSE., 1951)
Opera for the People was first published in 1951. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions. Everyone who enjoys opera will enjoy this book, and many who think they don't like opera will be delighted to discover how they can enjoy it. As Herbert Graf points out, opera in America today is not all it could be, and he shows how opera can be developed into something more vitala real force in the musical life of communities. As the long-time stage director of the Metropolitan Opera community, Dr. Graf is a foremost authority on opera production. From his wealth of practical experience, from his careful study of what others have done, and from his creative yet realistic thinking come his challenging proposals for a new kind of opera in Americaopera for everyone. The elements of opera productionthe libretto, the music, the language, the sponsorship, the staging, the buildingare discussed. American opera as it is performed on Broadway, in community civic companies, in school workshops, in motion pictures, and in television is surveyed. In conclusion, Dr. Graf draws his exciting blueprint for the opera of the future. Illustrative anecdotes provide sidelights on many gamed musical personalitiesBruno Walter, Kurt Weill, Benjamin Britten, Lawrence Tibbett, Oscar Hammerstein II, and Gian Carlo Menotti, to name a few. Stories of many of the newer operashow they came to be written and what they are aboutare related. Music lovers who yearn for a "new deal" in opera, civic leaders anxious to develop opera in their own communities, and schools and colleges offering opera training will find this book a stimulating guide